1994
DOI: 10.1136/adc.71.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Is rice based oral rehydration therapy effective in young infants?

Abstract: Rice based oral rehydration therapy (ORT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other study centres were in Egypt (three trials) (el-Mougi 1988; Fayad 1993; el-Mougi 1996); Chile (two trials) (Guiraldes 1995a; Guiraldes 1995b); Mexico (two trials) (Maulen-Radovan 1994; Maulen-Radovan 2004); and one trial each was done in Australia (Wall 1997), Colombia (Bernal 2005), Madagascar (Razafindrakoto 1993), Malaysia (Iyngkaran 1998), Pakistan (Islam 1994), the Philippines (Santos Ocampo 1993), Romania (Nanulescu 1999), Sudan (Mustafa 1995), and Thailand (Intarakhao 2010). All but two trials were conducted in hospital settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other study centres were in Egypt (three trials) (el-Mougi 1988; Fayad 1993; el-Mougi 1996); Chile (two trials) (Guiraldes 1995a; Guiraldes 1995b); Mexico (two trials) (Maulen-Radovan 1994; Maulen-Radovan 2004); and one trial each was done in Australia (Wall 1997), Colombia (Bernal 2005), Madagascar (Razafindrakoto 1993), Malaysia (Iyngkaran 1998), Pakistan (Islam 1994), the Philippines (Santos Ocampo 1993), Romania (Nanulescu 1999), Sudan (Mustafa 1995), and Thailand (Intarakhao 2010). All but two trials were conducted in hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…A few trials reported the number of participants with vomiting (11 trials) (Patra 1982; Bhan 1987; el-Mougi 1988; Mohan 1988; Alam 1992; Islam 1994; Mustafa 1995, rice; Mustafa 1995, sorghum; Dutta 1998, adults; Dutta 1998, children; Iyngkaran 1998); hyponatraemia (six trials) (Dutta 1988; Guiraldes 1995a; Bhattacharya 1998; Dutta 2000; Zaman 2001; Ramakrishna 2008); hypokalaemia (two trials) (Bhan 1987; Zaman 2007); and development of persistent diarrhoea (two trials) (Fayad 1993; Faruque 1997). …”
Section: Resultsmentioning
confidence: 99%